Fenêtre en longueur, floor-to-ceiling opening or curtain wall? A critical review of the wall openings syntax in modernity - Carlos L. Marcos (Revista de Expresión Gráfica en la Edificación, 2021)
Le Corbusier, in the 1920s, proposed a grammar for the new language of reinforced concrete and steel architecture, modern architecture. His mythical houses built during that decade in collaboration with Pierre Jeanneret would constitute an extraordinarily influential cast in the theatre of modern architecture and in later years would serve as models to illustrate a theory that would see the light of day in the form of a text in 1926 as a foundational manifesto, “The Five Points of Architecture”. His fenêtre en longueur –a horizontal strip window– highlighted the non-bearing condition of the façade while appropriating the horizon and a continuous view from the interior. Neoplasticist architecture, however, directly influenced by Wright’s “organic destruction of the box”, proposed opening voids from floor to ceiling. Both rejected the idea of perforating the façade by simply cutting holes in it. Mies van der Rohe, the most rigorous in architectural detail and construction of modern architects, would propose the incipient idea of the curtain wall in his project for the Friedrichstrasse skyscraper in 1919, which he would materialise years later. In the following article, we will critically discuss the grammar of modernity and in particular with regard to the syntax of the wall openings.